“Politicas Contables En El Control De Inventarios De La Empresa Colbapi S.A., Provincia De Los Ríos” - Vergara Salavarria, Mariuxi Maribel (2018)
The activity concerning the sector Ferretero is characterized by being one of the most dynamic in terms of the contribution made to the economy of a particular place, so it is considered a section that evolves and contributes constantly that undoubtedly favors the economic sector; despite facing a market with several requirements to consider as price, quality, variety of articles and materials for sale, credit granted and finally the development of new technologies; In turn, it is indispensable to know the customers' needs, which will lead to making the most convenient decisions to forge a good investment and thus obtain profits.